Manganese(III)-based reaction of 1,1-diarylethenes and 2,3-pyrrolidinediones. a simple route to 4-ethenyl- and 4-ethyl-2,3-pyrrolidinedione derivatives - Ha, Nguyen Van; My Trinh, Le Thi (Vietnam Journal of Chemistry, 2015)
2,3-Pyrrolidinediones reacted with manganese(III) acetate dihydrate in the presence of 1,1-diarylethenes to give 4-(2,2-diaryl)ethenyl-2,3-pyrolidinediones and/or 4-(2-acetoxy-2,2-diaryl)ethyl-2,3-pyrrolidinediones in good yields. The distribution of reaction products depended on the nature of 4-substituent on benzene ring of the 1,1-diarylethene used. The reaction mechanism is discussed.